Impact of Arteriovenous Fistula Creation on Progression of Chronic Kidney Disease - Asmara Asrar, Zahid Rafique, Aurangzeb Afzal, Azhar Nasim, Ali Talal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: All guidelines recommend pre-emptive arteriovenous fistula (AVF) formation in late-stage chronic kidney disease (CKD) patients. New evidence shows that pre-emptive AVF can improve estimated glomerular filtration rate (eGFR) as well. Aim: To evaluate the beneficial effect of AVF on improvement of eGFR in pre dialysis patients of CKD stage 5 disease. Methodology: A total of one hundred CKD stage five pre-dialysis patients were included in this prospective cohort research from the Nephrology unit of Services Hospital Lahore (SHL). After receiving approval from the ethical review committee SHL, the study was performed from September 2021 to March 2022. Patients were separated into two groups. Fifty patients with arteriovenous fistula (AVF) were in Group AVF, whereas those in Group Non-AVF were only on conservative therapy as they opted for conservative treatment despite counseling about need for AVF and Renal Replacement Therapy (RRT) in future. Over the course of six months, both groups were monitored. The initial eGFR was measured immediately after the formation of AV fistula and monthly for next six months (Final eGFR). Results: The median age of the study population was 37 years in which the sixty percent of the males. The most common comorbid condition was hypertension (96%) and the main reason for late-stage renal disfunction was diabetic nephropathy (45%). We found statistically significant improved eGFR in AVF group as compared to the non-AVF group (p < 0.01). Conclusion: From the results of our study, it can be concluded that the creation of AV fistula in the pre-dialysis patient has a beneficial effect on improvement of eGFR and delaying the progression CKD.